2018
DOI: 10.1139/facets-2017-0080
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of natural antioxidants from olive oil with fig and date palm fruit extracts on biochemical and hematological parameters in rats treated with doxorubicin and γ-radiation

Abstract: The goal of this study was to determine the possible beneficial effect of olive oil (7 g/kg) with fig (1 g/kg) and date palm fruit (1 g/kg) extracts (OFD) on the toxicity hazards of doxorubicin (DOX) and (or) γ-radiation. The DOX-treated groups received doses of 2.5 mg/kg body weight via intravenous (IV) injection weekly for four consecutive weeks. Rats in the irradiated groups were exposed to whole-body γ-radiation with fractioned doses of 2 Gy weekly for four consecutive weeks. The OFD-treated groups receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Our findings are in agreement with Fouad et al (2019) who reported that prior to irradiation, oral administration of F. carica extract significantly increased WBC, PLT, lymphocyte, and neutrophil counts. Fathy et al (2018) found similar results with rats treated with figs and dates extract for four weeks after exposure to Adricin® (doxorubicin hydrochloride) and / or irradiation. The heamatotoxic effect of nickel is primarily due to the over-stimulation of metallothioneins and reactive oxygen species (ROS) production that leads to erythrocyte oxidative damage.…”
Section: Discussion Discussion Discussionsupporting
confidence: 72%
“…Our findings are in agreement with Fouad et al (2019) who reported that prior to irradiation, oral administration of F. carica extract significantly increased WBC, PLT, lymphocyte, and neutrophil counts. Fathy et al (2018) found similar results with rats treated with figs and dates extract for four weeks after exposure to Adricin® (doxorubicin hydrochloride) and / or irradiation. The heamatotoxic effect of nickel is primarily due to the over-stimulation of metallothioneins and reactive oxygen species (ROS) production that leads to erythrocyte oxidative damage.…”
Section: Discussion Discussion Discussionsupporting
confidence: 72%
“…The excess energy in the adipocyte is stored in form of TAG and contributes to adipocyte hypertrophy and hyperplasia [34]. Additionally, the high levels of TAG can be regarded as a consequence of imbalances in the rate of synthesis and release of TAG by the parenchymal cells into the systemic circulation [35]. Administration of fenofibrate decreases serum TAG through activation of lipoprotein lipase [36] and enhancing fatty acid beta oxidation by activating PPAR alpha [37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to boost the antioxidant capacity and reduce releasing of free radicals [80]. Functional foods, such as olive oil, fig, and date palm, were good sources of exogenous antioxidants and are used in traditional medicine to manage various diseases [30,81,82]. Our results showed that FOD effectively ameliorated blood coagulation, endothelial dysfunction, and myocardial enzyme parameters induced by the NP administration indicating that FOD treatments have beneficial effects as antioxidants and protect against cardiovascular diseases [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…The extravirgin olive oil (7 g/kg.b wt.) and the fig and date palm fruit extracts (1 g/kg.b wt) were supplemented on rats orally and daily by gavage [30]. The different human-recommended antioxidant doses of the used materials were calculated and converted to rat doses [31].…”
Section: Preparation Of Crude Extractsmentioning
confidence: 99%